THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE IN COMPANIES LISTED ON THE IDX ESG LEADERS INDEX FOR 2021-2023 - Lu'luil Cindy Primadhani; Susi Handayani; Manuel Aristo Surbakti (JURASIMA, 2024)
This research aims to determine the influence of Good Corporate Governance and Corporate Social Responsibility on company value with financial performance as an intervening variable in companies listed on the IDX ESG Leaders Index for 2021-2023. This research uses a quantitative approach. The sample in this study was 46 companies listed on the IDX ESG Leaders Index for 2021-2023. The research results show that Good Corporate Governance and Corporate Social Responsibility have no effect on company value. Financial performance as an intervening variable is only able to mediate the influence of the Board of Directors, Independent Commissioners, and Corporate Social Responsibility on company value. However, financial performance is unable to mediate the influence of the Audit Committee on company value.